2020
DOI: 10.15244/pjoes/117694
|View full text |Cite
|
Sign up to set email alerts
|

A novel 3D-QSA<sup>2</sup>R Model Assisted with a Log-Normalized Method and Its Application in Molecular Modification

Abstract: Although chemical substances are beneficial to human life, large quantities of these chemicals flow into the environment as they are used and released. The transport of chemical substances in multiple environmental media widens the damage scope of these chemicals to the ecological environment and increases the difficulty of controlling chemical pollution. Atmospheric transport is the major pathway for the transport and redistribution of chemical pollutants in the environment of land and water bodies [1-2]. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…As compared to the final phytodegradation product of PCB-52, the migration of the final P1 phytodegradation product is still lower. This result is found to be consistent with the design concept [ 16 , 32 , 33 ]. In addition, the estrogenic toxicity and the migration of the final P1 phytodegradation product also showed a significant improvement as compared to the final PCB-52 phytodegradation product.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…As compared to the final phytodegradation product of PCB-52, the migration of the final P1 phytodegradation product is still lower. This result is found to be consistent with the design concept [ 16 , 32 , 33 ]. In addition, the estrogenic toxicity and the migration of the final P1 phytodegradation product also showed a significant improvement as compared to the final PCB-52 phytodegradation product.…”
Section: Discussionsupporting
confidence: 88%
“…Based on the CoMFA method, the results showed that the best principal component n and the cross-validation coefficient q 2 of the constructed 3D-QSAR model were 8 and 0.695 ( q 2 > 0.5), respectively, which indicates that the model exhibited good estimation ability. The non-cross-validation coefficient R 2 , the standard deviation SEE, and the test value F were estimated as 0.914 ( R 2 > 0.9), 2.854, and 67.952, respectively, which indicates that the constructed model fulfilled the stability requirements and exhibited good fitting and estimation abilities [ 32 ]. Based on the CoMFA method, Figure 2 shows the linear fit plots of the experimental and estimated values of the 3D-QSAR model for the phytotoxicity of PCBs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations